Seleção fenotípica e perdas de produção em pimenteiras (Capsicum annuum L.) ocasionadas por Ameiva ameiva L. e Tropidurus hispidus Spix. - Silva, Kadson Emmanuel Frutuoso (2019)
The pepper plants belong to the genus Capsicum and are an important segment of the ornamental plant market in Brazil. It has been growing steadily due to the demand for new products. The aim of this study was to analyze the genetic diversity, genotypic and phenotypic correlations and production losses in ornamental pepper plants. The experiments was conducted in a greenhouse in the Laboratory of Plant Biotechnology, from the Center for Agrarian Sciences at the Federal University of Paraíba (CCA / UFPB), Areia-PB. For this, the work was divided into three chapters. In chapter I the objective was to evaluate the genetic diversity in F3 populations of ornamental pepper plants (Capsicum annuum L.). Forty segregating populations and 4 witnesses were evaluated based on 15 quantitative descriptors. The experimental design was completely randomized with five plants per population. Data were subjected to analysis of the relative importance of characters determined by the Singh method, canonical variables analysis and the Scott-Knott test. In the second chapter were analyzed the genetic and phenotypic correlations for 31 agronomic characters between 5 segregating populations and two pepper tree witnesses. The experimental design was completely randomized four repetitions. Data were submitted to analysis of variance, means test (Tukey 5%) and analysis of genotypic and phenotypic correlations. In the third chapter were evaluated the production losses caused in the pepper (C. annuum L.) culture by the Ameiva ameiva and Tropidurus hispidus lizards. Three genotypes of pepper were used, differing in color of ripe fruit (red, yellow or orange). The experimental design was completely randomized in split plots with fourteen replications. Data were subjected to analysis of variance with later means test (Tukey 5%) and regression analysis. In Chapter I, Singh's method determined that 78.8% of the genetic diversity found is attributed to eight traits. The first three canonical variables represent 70% of the total variation. The sames grouped into six groups by the Scott Knott test. In the correlation analysis obtained in chapter II, positive correlations were detected between the of germination and vigor variables with the weight one hundred seeds variable. Positive correlations were observed between variables (AP / DC) and fruits (CFR, MDF, PF, CF). In the third chapter increasing losses were observed in the three genotypes during the evaluation days, whose largest production losses were on the fifth assessment day with damage exceeding 80%.